Employee Performance Reviewed From Incentives, Work Environment, Discipline And Leadership Style At Kratonan Community Health Center, Surakarta - Dwi Jayanti, Gigih; Istiatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence simultaneously (simultaneously) and partially of incentive variables, work environment, discipline and leadership style on employee performance at the Kratonan Surakarta Community Health Center. This research method uses a quantitative research design. The population in this study were 53 employees who worked at the Kratonan Surakarta Community Health Center. The sampling technique used in this research was a census technique with a sample size of 53 respondents. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that incentives, work environment, discipline and leadership style partially and significantly influence employee performance at the Kratonan Surakarta Community Health Center. The advice from this research is that the Kratonan Surakarta Community Health Center continues to improve incentives, work environment, discipline and existing leadership styles, so that employee performance will increase and be better than before.